Prediction of Pregnancy Outcome by Combined Analysis of the Fetal Electrocardiogram and Systolic Time Intervals - Lewinsky, Reuven M.; Sharf, Mordechai; Degani, Shimon; Eibschitz, Izu (American Journal of Perinatology, 1992)
A microcomputer-based system has been developed that continuously analyzes the fetal electrocardiogram (ECG) and Doppler cardiogram during labor by noninvasive means. Three systolic time intervals (preejection period [PEP], ventricular ejection time [VET], and isovolumetric contraction time), and four ECG parameters (P-R interval, QRS wave duration, T/QRS amplitude ratio, and S-T slope) are simultaneously measured and displayed. Normal values were derived from 126 uncomplicated pregnancies at term. A second group of 89 cases showing fetal heart rate patterns suggestive of fetal distress were subsequently studied: 64 had a good outcome (umbilical artery pH 7.20 or higher and a 5-minute Apgar score 7 or greater) and 25 were asphyxiated. Results were retrospectively analyzed. All asphyxiated fetuses had preejection period, PEP to VET ratio and T to QRS ratio values of more than 1 SD above the mean for the normal population. The PEP to VET ratio, which is an indicator of myocardial function independent of heart rate, proved to be the most sensitive predictor of fetal asphyxia. We conclude that analysis of systolic time intervals and ECG parameters of the fetal heart during labor improves the diagnostic accuracy of fetal heart rate monitoring.